A comparison of fluid status determination using bioelectric impedance and the isotope dilution method in hemodialysis and peritoneal dialysis patients. Issue 1 (31st December 2022) - Dou, Yanna; Gong, Yanan; Li, Afang; Wang, Peipei; Song, Dongyan; Wang, Yuyang; Liu, Dong; Cheng, Genyang; Zhao, Zhanzheng
Abstract: We aimed to compare fluid status as determined by multifrequency bioimpedance spectroscopy (MF-BIS, Xitron 4200, USA) with that determined by the isotope dilution method among a contemporary Chinese cohort. Healthy Chinese subjects (HS, n  = 30) were recruited in Zhengzhou. Hemodialysis (HD, n  = 49) and peritoneal dialysis (PD, n  = 48) patients were screened at the First Affiliated Hospital of Zhengzhou University. Total body water (TBW) and extracellular water (ECW) were measured by deuterium (TBWD ) and bromide (ECWBr ) dilution, respectively, and by MF-BIS using the Moissl equation (ME). The results of MF-BIS were compared to the reference method by Pearson analysis and Bland–Altman analysis in the three groups. The accuracy of overhydration as determined by MF-BIS was analyzed by receiver operating characteristic (ROC) curves. The TBWD and TBWME values were 34.67 ± 7.31 and 35.41 ± 5.76 L, 37.30 ± 8.58 and 37.02 ± 8.10 L, and 38.61 ± 10.02 and 38.44 ± 7.59 L in the HS, HD and PD groups, respectively. The ECWBr and ECWME values were 14.88 ± 3.33 and 15.53 ± 2.39 L, 16.24 ± 5.08 and 16.90 ± 3.93 L, and 19.08 ± 6.41 and 18.23 ± 3.61 L in the HS, HD and PD groups, respectively. The mean bias between TBWD and TBWME was −0.74 L, 0.28 L, and 0.17 L in the HS, HD and PD groups, respectively. The mean bias between ECWBr and ECWME was −0.65 L, −0.66 L, and 0.85 L in the HS, HD and PD groups, respectively. Compared to the ECWBr /TBWD ratio, the area under the ROC curve (AUC) of the ECWME /TBWME ratio for the diagnosis of overhydration was 0.76 and 0.68 in the HD and PD groups, respectively. In summary, MF-BIS with ME could be used in Chinese HD and PD patients.